DESAIN SISTEM INFORMASI PENYIMPANAN DAN PENGEMBALIAN REKAM MEDIS DENGAN METODE V-MODEL - Nafa Alifah Fitriany (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
A hospital medical record loan and retrieval system is an important process in the management of patient medical record files. This process ensures that only authorized individuals can access patient medical information for specific purposes. The borrowing and returning of medical record files must be properly monitored and controlled to reduce the occurrence of lost medical record files in hospitals. This research is motivated by the borrowing and returning system at AMC Hospital which is still done manually, making it difficult for officers to record the borrowing and returning of medical record files. The purpose of this research is to develop a loan and return information system that was previously done manually to be computerized, making it easier for officers to record borrowing and returning medical record files more effectively. Therefore, a concept of designing an information system for borrowing and returning medical record files is needed in the form of a program. The development method carried out in this research is to use the V-model method, and is implemented using Microsoft Visual Studio 2010 and Microsoft Access. The results of this study are expected to facilitate medical record officers in recording the process of borrowing and returning medical record files quickly and effectively.